Discrepancies between judgment and choice of action in moral dilemmas - Sébastien eTassy; Sébastien eTassy; Olivier eOullier; Julien eMancini; Julien eMancini; Bruno eWicker (Frontiers in Psychology, 2013)
Everyone has experienced the potential discrepancy between what one judges as morally acceptable and what one actually does when a choice between alternative behaviors is to be made. The present study explores empirically whether judgment and choice of action differ when people make decisions on dilemmas involving moral issues. 240 participants evaluated 24 moral and non-moral dilemmas either by judging (Is it acceptable to…) or reporting the choice of action they would make (Would you do…). We also investigated the influence of varying the number of people benefiting from the decision and the closeness of relationship of the decision maker with the potential victim on these two types of decision. Variations in the number of beneficiaries from the decision did not influence judgment nor choice of action. By contrast, closeness of relationship with the victim had a greater influence on the choice of action than on judgment. This differentiation between evaluative judgments and choices of action argues in favor of each of them being supported by (at least partially) different psychological processes.